2022
DOI: 10.1096/fj.202101803r
|View full text |Cite
|
Sign up to set email alerts
|

Controlled dual release of dihydrotestosterone and flutamide from polycaprolactone electrospun scaffolds accelerate burn wound healing

Abstract: Wound healing is a complex process involving multiple independent and overlapping sequential physiological mechanisms. In addition to cutaneous injury, a severe burn stimulates physiological derangements that induce a systemic hypermetabolic response resulting in impaired wound healing. Topical application of the anti‐androgen drug, flutamide accelerates cutaneous wound healing, whereas paradoxically systemic dihydrotestosterone (DHT) improves burn wound healing. We developed and characterized a PCL scaffold t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…PGA and PLCL have been used as a vehicle for cell therapy or bioactive factors to promote repair. [22][23][24][25] For example, to improve vascularization or treat stenosis that occurred in previous studies, VEGF and Mitomycin C can be added to the polymers. [26][27][28][29] We demonstrated that these materials can be easily implanted and demonstrate early revascularization, facets which are imperative in future use as therapeutic solutions being in close proximity to areas of wound repair and regeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PGA and PLCL have been used as a vehicle for cell therapy or bioactive factors to promote repair. [22][23][24][25] For example, to improve vascularization or treat stenosis that occurred in previous studies, VEGF and Mitomycin C can be added to the polymers. [26][27][28][29] We demonstrated that these materials can be easily implanted and demonstrate early revascularization, facets which are imperative in future use as therapeutic solutions being in close proximity to areas of wound repair and regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the resorbable biomaterials in CTG did not attenuate tracheal neotissue formation. PGA and PLCL have been used as a vehicle for cell therapy or bioactive factors to promote repair 22–25 . For example, to improve vascularization or treat stenosis that occurred in previous studies, VEGF and Mitomycin C can be added to the polymers 26–29 .…”
Section: Discussionmentioning
confidence: 99%